Sistem Pakar Diagnosa Penyakit Kucing Dan Anjing Menggunakan Metode Naïve-Bayes Dan Certainty Factor Berbasis Web - Rama Adistya Nurtjahya Pramudji (IKRAM: Jurnal Ilmu Komputer Al Muslim, 2024)
for pets like cats and dogs involves various aspects such as feeding, hygiene, and health, especially in disease-prone environments. Many pet owners lack knowledge in providing proper care and medical attention.Creating an expert system for diagnosing diseases using methods like naive bayes and certainty factor can aid in accurate and timely assistance to pet owners.These methods offer a reliable approach based on probability and evidence, ensuring more precise diagnostic outcomes.